Qualidade da água do rio Pará do Uruará: o caso do distrito de Santa Maria do Uruará do município de Prainha, Pará, Brasil - FLEXA, Gustavo da Silva (Universidade Federal do Oeste do Pará, 2022)
The decrease in the water quality of rivers in the Amazon is notorious due to anthropogenic factors associated with the release of effluent into the water. In this perspective, this study aimed to evaluate the water quality of the Pará do Uruará River bordered by a riverside community, as an investigation of possible changes in water quality due to the discharge of domestic and sanitary wastewater, fires and suppression of trees along the river. The study area is the surface waters surrounding the District of Santa Maria do Uruará, in the municipality of Prainha, western Pará, Brazil. Nine sampling points were defined in a 4 km stretch, distributed in sampling units classified as upstream (P3), intermediate (P2) and downstream (P1). In each sampling unit, three water samples were collected in the cross section of Rio. The parameters evaluated were: temperature, pH, dissolved oxygen, total residue, biochemical oxygen demand, thermotolerant coliforms, total nitrogen, total phosphorus and turbidity. The evaluation of the results was carried out by descriptive statistical analysis and application of the Water Quality Index (IQA). In the results of the parameters, we observed better quality indices in the upstream when compared to the intermediate and downstream points, suggesting that the water quality is affected by anthropic actions in the district. It is suggested the need for mitigation actions that promote the environmental education of the population and implement measures to improve the drainage system and effluent treatment, aiming to avoid river contamination and ensure quality water resources.